Earnings management around the Tax Cuts and Jobs Act of 2017 - Lynch, Daniel P.; Pflitsch, Max; Stich, Michael (Review of Accounting Studies, 2026)
This paper examines earnings management in response to changes in tax planning and financial reporting incentives around the corporate income tax rate decrease from 35% to 21% enacted by Tax Cuts and Jobs Act (TCJA) of 2017. Given the higher level of book-tax conformity of real activities manipulation (RAM) relative to accrual-based earnings management (AEM), we hypothesize that firms concertedly use these techniques for different purposes. Specifically, we predict and find that firms use RAM to reduce taxable income prior to the TCJA with firms in our sample saving between $9.1 billion and $11.0 billion in taxes by shifting taxable income from the high-tax to the low-tax period. We also predict and find that firms use AEM, which has lower book-tax conformity than RAM, to simultaneously increase book income in the high-tax period. These results inform policymakers, regulators, and researchers on the economic effects of corporate tax reform.